Sulfur Dioxide Transported From the Residual Layer Drives Atmospheric Nucleation During Haze Periods in Beijing. Issue 6 (14th March 2023) - Wang, Yonghong; Ma, Yongjing; Yan, Chao; Yao, Lei; Cai, Runlong; Li, Shuying; Lin, Zhuohui; Zhao, Xiujuan; Yin, Rujing; Deng, Chenjuan; Kangasluoma, Juha; He, Xu‐Cheng; et al.
Abstract: New particle formation (NPF) is a global phenomenon that significantly influences climate. NPF also contributes to haze, with pronounced negative impacts on human health. Theory and observations both show that nucleation is favored during clean days and inhibited during haze episodes due to a high pre‐existing condensation sink (CS). Here we show that the surprising occurrence of NPF during haze days in Beijing is associated with a high concentration of sulfuric acid dimers. With both field observations and model simulations, we demonstrate that downward mixing of sulfur dioxide (SO2 ) from the residual layer aloft enhances ground level SO2, which in turn elevates sulfuric acid dimer after rapid SO2 oxidation in the polluted air. Our results address a key gap between the source of SO2 and its atmospheric oxidation products during haze conditions in a megacity, Beijing, providing a missing link in a complete chain describing NPF in the polluted atmosphere. Plain Language Summary: New particle formation is a global phenomenon with notable effects on climate and health. Recent studies have argued that atmospheric nucleation during haze episodes with high aerosol loading should not occur. In spite of this, we have observed intensive nucleation events during haze episodes in Beijing and found an unexpected high concentration of sulfur dioxide (SO2 ), along with a decreased condensation sink (CS) owing to the development of boundary layer. The SO2 originates from emissions by tall stacks outside of Beijing and is subsequently transported downward from the morning residual layer to the surface, this contributes to peaks of SO2 during the day. A decreased loss of sulfuric acid dimer owing to a decreased CS drives nucleation during haze episodes. As the phenomenon of a later morning SO2 peak exactly coincide with nucleation has been widely reported in eastern China, we highlight the importance of emissions of SO2 from tall smokestacks in atmospheric nucleation events. Key Points: Sulfuric acid dimer is involved in new particle formation (NPF) events during haze episodes in Beijing Field observation and model simulation confirm downward mixing of sulfur dioxide from residual layer High formation rate of sulfuric acid dimer owing to a decreased condensation sink promotes NPF during haze